Psychoanalysis and Islam: The Father in Islam and in Anthropological Reality - Fethi Benslama (EJP import test, 2019)
[caption id="attachment_2350" align="alignleft" width="1024"] "Alien" by Stephen Mosblech[/caption] Presented at «Il padre oggi» Conference (organized by the Istituto Psicoanalitico per la Ricerca Sociale and by I.R.E.P.) Rome, La Sapienza University, October 26-27, 2019